Availability And Geographic Access To Breast Cancer Pathology Services In Ghana. - Dey, D.; Hodkinson, B. (Clinical Rheumatology, 2025)
Tremendous strides have been made in rheumatology in Africa, with advances in patient care, access to therapies, training, and research noted across the continent [1]. There is still much to do on the world’s poorest continent which carries about 40% of the global burden of disease. Recent work highlights the suboptimal knowledge and management of rheumatic and musculoskeletal diseases (RMD’s) among doctors working in Africa. An online survey of rheumatologists, nephrologists, dermatologists, and specialist physicians across Africa revealed that low awareness, lack of access to specialist care, and misdiagnosis as Human Immunodeficiency Virus (HIV) or Tuberculosis contributed to the late diagnosis of Systemic Lupus Erythematosus (SLE) [2]. Significantly, 91% of respondents regarded late diagnosis as a reason for poor outcomes. Similarly, a survey of African clinicians described barriers to prescribing methotrexate (MTX) for RMD’s including the limited numbers of trained rheumatologists, and uncertainty of the safety of MTX in persons with comorbidities and endemic infections [3]. Regarding axial spondyloarthritis, in South Africa a diagnostic delay of almost 11 years was reported, associated with a high disease burden and a significant prevalence of poor mental health (69.9%) [4]. Interviews with Kenyan healthcare workers highlighted their perceived lack of knowledge and low competence in managing pediatric rheumatology patients [5]. Challenges lie ahead: many RMD’s are on the rise in Africa due to lifestyle factors, population growth, and ageing. Gout is increasing exponentially in sub-Saharan Africa (SSA); by 2050, the number of cases is predicted to increase by more than 250% [6]. Low back pain is the largest contributor to years lived with disability, and by 2050, the number of cases is expected to increase by 36,4% globally, with the most substantial increases expected in Asia and Africa [7]. Osteoarthritis is common in Africa with a pooled prevalence of 14.2% and is increasing in low- and middle-income countries of SSA [7]. Osteoporosis and associated fragility fractures are a growing major concern in Africa [8]. The global burden of RA is expanding, with early diagnosis and aggressive treatment hampered by low disease awareness and delays in referring and initiation therapy, often driven by socioeconomic factors [9, 10]. How can we tackle these challenges when rheumatology education and resources in Africa remain significantly underdeveloped compared to high-income countries.? This disparity is driven by a variety of factors, including insufficient educational resources, a critical shortage of trained rheumatologists, and limited access to specialized training. However, solutions need to be found. “It is not because countries are poor that they cannot afford good health information. It is because they are poor that they cannot afford to be without it”
Research Article
Keywords: MEDICINE::Dermatology and venerology,clinical genetics, internal medicine::Internal medicine::Rheumatology; Gap; Africa